PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN PEMAHAMAN SISWA - masrikan, masrikan (Jurnal Penelitian Pembelajaran Fisika, 2012)
ABSTRAKThe learning of physics today is still far from what is expected in the present curriculum. The grades are very low. The studentâs interest and creativity in physics learning are low. Studentâs desire to learn actively and to deeper learn physics is still low. Based on the fact, it is necessary to build a learning model which can improve comprehension in the learning of physics. The background student in SMP 38 come from the middle and under economic family. The model should be easy for teachers to adopt, and also easy for the students. In the research the humanistic approach is chosen, in this case a humanistic approach which is applicable to improve students comprehension in SMP 38 Semarang.The research is aimed at implementing the humanistic approuch to improve studentsâ comprehension in the learning of physics in junior high school students. Studentsâ comprehension in learning increases to 19,80 in the before research up to 30,68 in the four cycle. Learning achievement has not reach the did wished standart yet. It shows that physics learning model using problem based can increase studentâs comprehension. The increasing of the comprehension will improve studentâs learning motivation. And learning achievement will be reached when there is learning habit which caused by the improvement of studentâs motivation.Key Words : humanistic approach, comprehension, physics learning.